2017
DOI: 10.1177/0956247817692200
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the nature and scale of risks in Karonga, Malawi

Abstract: The urban centre of Karonga in Malawi experiences many large and small disasters, including earthquakes, strong winds and floods. Inhabitants also face such everyday risks as unsafe water, poor-quality sanitation and widespread use of dirty fuels within households. However, the nature and scale of the risks are poorly understood. Based on data from 380 systematically selected households in Karonga, this paper explores the frequency and impacts of small and large disasters and everyday risks, finding informal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…As stagnant water pools become breeding sites for mosquitoes malaria was prevalent (23.42 %) in the study area ( Figure 5). It is worth noting that the WASH related risks contribute to everyday risks that lead to premature deaths among the majority of residents in the town.Similar observations were also made by Manda and Wanda (2017), who reported that inadequate provision for WASH services is one of the everyday risks impacting on the population, especially those from low income areas of the town. Manda and Wanda (2017) also observed that the majority of the population in Karonga Town lived in flood-prone areas, specifically along rivers, where flooding was annual.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…As stagnant water pools become breeding sites for mosquitoes malaria was prevalent (23.42 %) in the study area ( Figure 5). It is worth noting that the WASH related risks contribute to everyday risks that lead to premature deaths among the majority of residents in the town.Similar observations were also made by Manda and Wanda (2017), who reported that inadequate provision for WASH services is one of the everyday risks impacting on the population, especially those from low income areas of the town. Manda and Wanda (2017) also observed that the majority of the population in Karonga Town lived in flood-prone areas, specifically along rivers, where flooding was annual.…”
supporting
confidence: 81%
“…Nevertheless, some waterborne diseases such as cholera (18.68%), diarrhea (6.05%) and dysentery (6.58%) were reported to be Wanda et al Figure 5). Occurrence of such diseases was largely attributed to use and consumption of contaminated water by the affected members of the community in Karonga Town (Manda and Wanda, 2017). …”
mentioning
confidence: 99%
“…Everyday risks such as poor quality and inadequate sanitation and unsafe water also pose significant threats for inhabitants [23]. However, the nature and scale of risks in Karonga remains poorly understood and knowledge of vulnerabilities to disaster risks remain low [24]. This is partly attributable to the lack of political attention and finance towards the development and governance of small, but often rapidly growing towns throughout Malawi and indeed other sSA contexts more broadly [22].…”
Section: Karonga Malawimentioning
confidence: 99%
“…However, the policy has some notable weaknesses that are limiting effective implementation. For instance, Malawi's urban areas are not specifically addressed despite the increasing trend of urban disasters such as flooding and resource allocation to lower governance scales being highly inadequate [24]. Furthermore, the disaster management structures included in the Disaster Risk Management Policy exist largely only on paper with limited capacity and practical knowledge for addressing risks and risk accumulation.…”
Section: Karonga Malawimentioning
confidence: 99%
See 1 more Smart Citation